Features of complex therapeutical rehabilitation management with favorable evolution in a patient with right hemiplegia, mixed aphasia and optic atrophy post surgical removal of benign intraventricular tumor (central neurocytoma) - a case report (Balneo and PRM Research Journal, 2022)
AbstractIntroduction: Central neurocytoma (CN) is a benign brain tumor located intraventricularly and classified as grade II by the World Health Organization in 2000 (classification of tumours of the central nervous system). CN is frequently found in young adults and may increase intracranial pressure causing obstructive hydrocephalus, manifested by neurological symptoms such as headaches and vision problems. CN has a relatively good prognosis, provided a complete surgical resection is performed.Materials and Methods: In this presentation, we describe the case of a 21-year-old patient with a personal history of headache, vomiting and decreased visual acuity in both eyes, who was admitted to the Neurosurgery Clinic III of THEBA. Following clinical and paraclinical assesements, the patient was diagnosed with a left lateral ventricular tumor with extension in the right lateral ventricle and the third ventricle. The neurosurgery team decided a total resection of the tumor would be the best approach in this case. The biopsy report revealed that it was a central neurocytoma. After the surgery the patient’s neurological status improved and she was admitted in the Neuromuscular Rehabilitation Cinical Division with flaccid right hemiplegia and mixed aphasia. The patient was functionally assessed using the following scales: Functional Independence Measure (FIM), Montreal Cognitive Assessment (MOCA), modified Ashworth, Penn Spasm Frequency Scale (Penn), Life Quality Assessment (QOL), FAC International Scale, Glasgow Outcome Scale-Extended (GOS-E), modified Rankin scale (mRS), Aphasia Screening Test (AST-Whurr).Results: The patient showed a favorable evolution with remitted aphasia and walking traing with self-support in tertrapod walking stick. At the same time, the patient can use the plegic upper limb in performing feeding activities.Conclusion: It should be noted that neurosurgical intervention and pharmacological treatment, associated with an individual rehabilitation program consisting of: physical, occupational and speech therapies and also rehabilitation nursing interventions in a patient diagnosed with flaccid right hemiplegia and mixed aphasia after total surgical resection of the intraventricular central neurocytoma has improved the control of symptoms and the patient's quality of life.Keywords: benign brain tumor, central neurocytoma, hemiplegia, rehabilitation